Identification of MicroRNAs and Their Target Genes Related to the Accumulation of Anthocyanins in Litchi chinensis by High-Throughput Sequencing and Degradome Analysis - Liu, Rui; Lai, Biao; Hu, Bing; Qin, Yonghua; Hu, Guibing; Zhao, Jietang (Frontiers in Plant Science, 2017)
Litchi (Litchi chinensis Sonn.) is an important subtropical fruit in southern China and the fruit pericarp has attractive red skin at maturity, which is provided by anthocyanins accumulation. To understand the anthocyanin biosynthesis at post-transcriptional level, we investigated the roles of microRNAs (miRNAs) during fruit coloring. In the present study, four small RNA libraries and a mixed degradome library from pericarps of ‘Feizixiao’ litchi at different developmental phases were constructed and sequenced by Solexa technology. A total of 78 conserved miRNAs belonging to 35 miRNA families and 41 novel miRNAs were identified via high-throughput sequencing, and 129 genes were identified as their targets by the recently developed degradome sequencing. miR156a and a novel microRNA (NEW41) were found to be differentially expressed during fruit coloring, indicating they might affect anthocyanin biosynthesis through their target genes in litchi. qRT-PCR analysis confirmed the expression changes of miR156a and the novel microRNA (NEW41) were inversely correlated with the expression profiles of their target genes LcSPL1/2 and LcCHI, respectively, suggesting regulatory roles of these miRNAs during anthocyanin biosynthesis. The target genes of miR156a, LcSPL1/2, encode transcription factors, as evidenced by a localization in the nucleus, that might play roles in the regulation of transcription. To further explore the relationship of LcSPL1/2 with the anthocyanin regulatory genes, yeast two-hybrid and BiFC analyses showed that LcSPL1 proteins could interact with LcMYB1, which is the key regulatory gene in anthocyanin biosynthesis in litchi. This study represents a comprehensive expression profiling of miRNAs in anthocyanin biosynthesis during litchi fruit maturity and confirmed that the miR156- SPLs module was conserved in anthocyanin biosynthesis in litchi.